Electrical, thermal, and dielectric studies of ionic liquid-based polymer electrolyte for photoelectrochemical device. (October 2018) - Dhapola, Pawan S; Singh, Pramod K; Bhattacharya, B; Surana, Karan; Mehra, RM; Gupta, Meenal; Singh, Abhimanyu; Singh, Vijay; Sahoo, Nanda G
In this work, solution cast method was adapted for the preparation of 1-ethyl-3-methylimidazolium dicyanamide (EMImDCN)-doped solid polymer electrolyte. Optimum composition of polymer electrolyte (polyethylene oxide + sodium iodide) was treated as the host polymer. The ionic conductivity was further enhanced by adding low-viscosity ionic liquid (IL) EMImDCN. Electrical, thermal, dielectric, and photoelectrochemical properties of polymer host and IL-doped solid polymer electrolyte (ILDPE) are presented in detail. An electrochemical device, that is, dye-sensitized solar cell was fabricated using maximum conducting ILDPE film, which shows short-circuit current density of 0.118 mA/cm 2, open-circuit voltage of 0.71 V, and overall efficiency of 0.061% at 1 sun condition.